Understanding the chemistry behind the antioxidant activities of butylated hydroxytoluene (BHT): A review - Yehye, Wageeh Abdulhadi; Abd Rahman, Noorsaadah; Ariffin, Azhar; Hamid, Sharifah Bee Abd; Alhadi, A.A.; Kadir, F.A.; Yaeghoobi, M. (Elsevier, 2015)
Hindered phenols find a wide variety of applications across many different industry sectors. Butylated hydroxytoluene (BHT) is a most commonly used antioxidant recognized as safe for use in foods containing fats, pharmaceuticals, petroleum products, rubber and oil industries. In the past two decades, there has been growing interest in finding novel antioxidants to meet the requirements of these industries. To accelerate the antioxidant discovery process, researchers have designed and synthesized a series of BHT derivatives targeting to improve its antioxidant properties to be having a wide range of antioxidant activities markedly enhanced radical scavenging ability and other physical properties. Accordingly, some structure–activity relationships and rational design strategies for antioxidants based on BHT structure have been suggested and applied in practice. We have identified 14 very sensitive parameters, which may play a major role on the antioxidant performance of BHT. In this review, we attempt to summarize the current knowledge on this topic, which is of significance in selecting and designing novel antioxidants using a well-known antioxidant BHT as a building-block molecule. Our strategy involved investigation on understanding the chemistry behind the antioxidant activities of BHT, whether through hydrogen or electron transfer mechanism to enable promising anti-oxidant candidates to be synthesized.